Cross-Linguistic Insights into Idiomatic Expressions: A Case of Human Body Idioms in English and Indonesian - Sulaiman, Masagus; Syahri, Indawan; Fadhilah, Mutiara (Journal of English Education, 2025)
Idiomatic expressions are essential parts of natural language use, helping speakers express complex ideas, emotions, and cultural values more effectively. However, they can pose difficulties for language learners due to their figurative nature and cultural dependency. This study aimed at finding out the similarities and differences between English and Indonesian idiomatic expressions. of human body. In this study, the researchers used a qualitative research design. The documentation technique was used to collect the data from primary and secondary data sources related to English and Indonesian Idiomatic expression books and journal. To analyse the data, thematic analysis was applied. The results showed that there were seventeen similarities in terms of nine in meanings and eight in forms, as well as six differences in word choices in terms of three in meanings and three in forms.  In conclusion, the similarities between English and Indonesian idiomatic expressions. of human body make no problems for students to learn English and Indonesian idiomatic expressions. Yet, the differences between English and Indonesian idiomatic expressions. of human body make students difficult to learn English and Indonesian idiomatic expressions.